A Randomized Controlled Trial of Meridian-Guided Fire Dragon Cupping and Moxibustion for Improving Limb Pain and Numbness in Diabetic Peripheral Neuropathy - Na, Liu (Journal of Contemporary Medical Practice, 2025)
Objective: To evaluate the clinical efficacy and safety of Meridian-Guided Fire Dragon Cupping and Moxibustion (MGFDCM) in improving limb pain, numbness, and nerve function in patients with diabetic peripheral neuropathy (DPN) presenting with the pattern of Qi deficiency and blood stasis. Methods: A randomized, single-blind, parallel-controlled trial was conducted. Seventy-two eligible patients were randomly assigned in a 1:1 ratio to either a treatment group or a control group n=36. Both groups maintained basic glucose-lowering and neurotrophic therapy. The treatment group received MGFDCM, while the control group received simulated cupping treatment, three times per week for 4 weeks. The primary outcome measures were pain and numbness symptom scores assessed using a Visual Analogue Scale (VAS). Secondary outcomes included the Toronto Clinical Neuropathy Score (TCSS), a Traditional Chinese Medicine (TCM) syndrome score, and nerve conduction velocity (NCV). Results: After treatment, improvement in the primary outcomes was significantly greater in the treatment group than in the control group: the mean reduction in VAS pain score was (4.2 ± 1.1) points versus (1.8 ± 0.9) points, and the mean reduction in numbness score was (3.5 ± 0.8) points versus (1.6 ± 0.7) points (all P < 0.01). For secondary outcomes, the treatment group also showed superior results: a lower post-treatment TCSS total score [(5.2 ± 2.1) vs. (8.9 ± 2.4), P < 0.01], a greater reduction in the TCM syndrome score [(12.5 ± 3.2) points vs. (5.8 ± 2.7) points, P < 0.01], and more pronounced improvements in the motor and sensory NCV of both the median and common peroneal nerves (all P < 0.05). During treatment, only two cases in the treatment group experienced transient local skin redness, and no serious adverse events were reported. Conclusion: Meridian-Guided Fire Dragon Cupping and Moxibustion is a safe and effective intervention for alleviating limb pain and numbness and for promoting nerve function recovery in DPN patients with the pattern of Qi deficiency and blood stasis. Its therapeutic effect is significantly superior to simulated treatment, warranting clinical application and promotion.